Faktor-Faktor yang Mempengaruhi Pengguna Gojek menggunakan Gopay - Tiar Lina Situngkir; Ratih Hurriyati; Mokh. Adib Sultan (Universitas Samudra, 2020)
This study aims to analyze the factors that influence Gojek customers using Gopay services. The population is the community of Singaperbangsa University, Karawang who actively use Gojek and Gopay services whose numbers are not clearly known. Samples were taken for analysis, from filling out the questionnaire as many as 118 respondents were received. The multiple regression analysis method represented by the independent variable consists of financial costs and benefits. The results of the analysis prove that only the benefit variable has a significant effect on the use of Gojek using Gopay services, the other variable is that financial costs do not significantly influence the use of Gopay services. This study has limited location, which can have an impact on the results of the study. In the future, subsequent researchers can further expand the research area.